2020
DOI: 10.1136/bmjdrc-2020-001403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes on exosomal miRNA profile in patients with obesity

Abstract: IntroductionObesity is a risk factor for type 2 diabetes mellitus (T2DM) and cardiovascular disease. T2DM increases the risk of cardiovascular-related death. We investigated changes in circulating exosomal microRNA (miRNA) profiles in patients with DM with obesity compared with patients without DM with obesity.Research design and methodsThis prospective study involved 29 patients with obesity (patients without DM=16, patients with DM=13) and healthy volunteers (HVs) (n=18). We measured circulating levels of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Furthermore, a recent prospective study demonstrated alteration of expression of 25 exosomal miRNA levels between patients with obesity with DM and patients with obesity without DM, highlighting affection of exosomal miRNAs by dysregulated glucose metabolism in patients with obesity. This supports their use as potential biomarker and therapeutic target in patients with obesity with or without DM (H. Kim et al, 2020). On the contrary, human MSC-derived exosomes has been found to be rich in glucose metabolism-associated proteins that promote glucose transporter 4 (GLUT4) expression, increase glycogen storage in liver to maintain glucose homeostasis, inhibit β-cell apoptosis, and improve peripheral insulin sensitivity in type 2 DM (Y. .…”
Section: Exosomes In Covid-19mentioning
confidence: 84%
“…Furthermore, a recent prospective study demonstrated alteration of expression of 25 exosomal miRNA levels between patients with obesity with DM and patients with obesity without DM, highlighting affection of exosomal miRNAs by dysregulated glucose metabolism in patients with obesity. This supports their use as potential biomarker and therapeutic target in patients with obesity with or without DM (H. Kim et al, 2020). On the contrary, human MSC-derived exosomes has been found to be rich in glucose metabolism-associated proteins that promote glucose transporter 4 (GLUT4) expression, increase glycogen storage in liver to maintain glucose homeostasis, inhibit β-cell apoptosis, and improve peripheral insulin sensitivity in type 2 DM (Y. .…”
Section: Exosomes In Covid-19mentioning
confidence: 84%
“…These exosomal miRNAs can be taken up by recipient cells, and in turn, they subsequently modulate recipient cells (Zhang et al, 2015). Exosomal miRNAs have a significant influence on a variety of diseases including cancer, diabetes, and cardiovascular disease (Chen et al, 2014; Emanueli et al, 2015; Kim et al, 2020). For instance, exosomal miR‐21 has been significantly correlated to liver metastasis and prognosis of colorectal cancer (Zhu, Huang, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigations are needed to explain the role of miRNAs in the RAGE–DIAPH1 signalling axis in DM and its neurological complications. The profile of expressed miRNAs and exosomal miRNAs are different in patients with diabetes compared with a control group (Gan et al, 2020; Kim et al, 2020). miRNAs therefore may be also excellent biomarkers for the detection of the onset of diabetic peripheral (length‐dependent) neuropathy (Feng et al, 2016; Hagiwara et al, 2013; Ma et al, 2017; Piperi et al, 2015).…”
Section: The Rage Diaph1 and Another Rage Ligands In Neurological Complications Of Dmmentioning
confidence: 99%